In Memoriam: Prof. Pranas Baltrėnas (1940–2021) - Grubliauskas, Raimondas (Journal of Environmental Engineering and Landscape Management, 2021)
“In memoriam: Prof. Prof. Pranas Baltrėnas (1940–2021)”. Journal of Environmental Engineering and Landscape Management, 29(2), pp. 72